Flies on the move: an inherited virus mirrors Drosophila melanogaster's elusive ecology and demography. Issue 8 (3rd April 2014) - Wilfert, Lena; Jiggins, Francis M.
Abstract Vertically transmitted parasites rely on their host's reproduction for their transmission, leading to the evolutionary histories of both parties being intimately entwined. Parasites can thus serve as a population genetic magnifying glass for their host's demographic history. Here, we study the fruitfly Drosophila melanogaster's vertically transmitted sigma virus DMelSV. The virus has a high mutation rate and low effective population size, allowing us to reconstruct at a fine scale how the combined forces of the movement of flies and selection on the virus have shaped its migration patterns. We found that the virus is likely to have spread to Europe from Africa, mirroring the colonization route of Drosophila. The North American DMelSV population appears to be the result of a recent single immigration from Europe, invading together with its host in the late 19th century. Across Europe, DMelSV migration rates are low and populations are highly genetically structured, likely reflecting limited fly movement. Despite being intolerant of extreme cold, viral diversity suggests that fly populations can persist in harsh continental climates and that recolonization from the warmer south plays a minor role. In conclusion, studying DMelSV can provide insights into the poorly understood ecology of D. melanogaster, one of the best‐studied organisms in biology.